Analisis Hukum Waris Islam terhadap Sistem Pembagian Waris pada Masyarakat Adat Kaur di Provinsi Bengkulu - Albiman Saputra; Mohammad Yasir Fauzi; Sisca Novalia (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
The diversity of inheritance systems in Indonesia reflects the interaction between Islamic law, customary law, and national law. This study examines the inheritance distribution practices of the Kaur indigenous community in Bengkulu Province, which adopts a bilateral system through family deliberation. The main focus is to analyze the compatibility of these practices with the principles of Islamic inheritance law. This research employs a descriptive qualitative method based on library study, utilizing primary data from the Qur’an, Hadith, the Compilation of Islamic Law (KHI), and relevant legislation, alongside secondary data from academic literature. The findings reveal that the Kaur community distributes inheritance flexibly through consensus, granting rights to both sons and daughters without strict proportional distinctions. A contextual notion of justice is emphasized, as reflected in practices such as gilir sawah (rotational use of farmland) as a form of collective asset management. From the perspective of Islamic law, this system is not entirely aligned with the faraidh provisions, which are definitive (qath’i), particularly regarding the proportional shares between male and female heirs as prescribed in Surah An-Nisa. Nevertheless, the principles of deliberation and social balance inherent in Kaur customary practice can serve as an entry point for harmonization with Sharia. This study underscores the importance of constructive dialogue among religious scholars, customary leaders, and state institutions to formulate an inheritance model that is just, contextual, and consistent with both Islamic principles and the national legal framework.